The Effect of Human Resource Competency, Infrastructure, Readiness, Organizational Culture, and Work Discipline on Improving Service Quality at the Batam City Fire and Rescue Service in Handling Emergency Situations - Rafeah, Rafeah; Ratnasari, Sri Langgeng; Susanto, Alpino (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study analyzes the factors that influence service quality in firefighting and rescue organizations by examining the role of competence, infrastructure, organizational culture, responsiveness, and work discipline. Using a quantitative approach with Structural Equation Modeling using Partial Least Squares (SEM-PLS), the results show that responsiveness is the strongest predictor of service quality, followed by infrastructure, indicating that timely action and adequate facilities are key factors in the delivery of effective emergency services. Work discipline shows a smaller but positive contribution, reflecting the relevance of procedural compliance in supporting operational performance. On the other hand, competency and organizational culture show a negative relationship with service quality, suggesting that higher expectations among skilled employees and strong cultural norms can lead to more critical evaluations of service conditions when operational realities do not match internal standards. Overall, these findings highlight that service quality in firefighting and rescue services is primarily influenced by responsiveness and structural readiness, while competence and culture function as evaluative filters shaped by employee perceptions. This study offers practical insights for improving service performance through enhanced response readiness, strengthened infrastructure, and better alignment between organizational expectations and operational support.